Inside Cover: Structural Elucidation of Selective Solvatochromism in a Responsive‐at‐Metal Cyclometalated Platinum(II) Complex (Angew. Chem. Int. Ed. 26/2020). Issue 26 (28th April 2020) - Soto, Miguel A.; Carta, Veronica; Andrews, Ryan J.; Chaudhry, Mohammad T.; MacLachlan, Mark. J.
Abstract : Platinum is king ! A responsive‐at‐metal platinum(II) emitter undergoes supramolecular and redox transformations on demand, as demonstrated by M. J. MacLachlan and co‐workers in their Communication on page 10348 . Pt II is selectively oxidized into Pt III or Pt IV, which diversifies the structural and photophysical properties of the emitter. Delicate modulation of the Pt⋅⋅⋅Pt interactions by solvent molecules results in strong vapo/solvatochromic effects.